War of the dragons - Shim, Hyung Rae; Kang, James B.; Jeong, Taesung; Choi, Sungho; Showbox (Firm); Younggu Art Production (Korea : Younggu Art Studio, 2008)
War of the Dragon' is based on a Korean legend of the Imoogi, which is a serpent that can transform into a dragon by possessing the'Yuh Yi Joo'. Dragon-like creatures from an ancient legend appear in Los Angeles and terrorise the city in search for a girl named Sarah. While investigating one of the disaster sites, TV reporter Ethan uncovers a piece of debris that directly links him to this legend. Ethan must realise his destiny as an ancient warrior who was re-born to protect Sarah from the evil dragon and save the city from total destruction
Bonus features: Trailer, highlight, interview and the making of
Title from title screen
Cast: Jason Behr, Amanda Brooks, Craig Robinson, Elizabeth Pena, Robert Forster
DVD Format
Optional subtitles in English, Chinese or Malay